2017
DOI: 10.5714/cl.2017.21.081
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium from tannery wastewater by electrosorption on carbon prepared from peach stones: effect of applied potential

Abstract: The objective of this study is the removal of chromium from tannery wastewater by electrosorption on carbon prepared from lignocellulosic natural residue "peach stones' thermally treated. The followed steps for obtaining coal in chronological order were: cleaning, drying, crushing and finally its carbonization at 900°C. The characterization of the carbon material resulted in properties comparable to those of many coals industrially manufactured. The study of the dynamic adsorption of chromium on the obtained m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The longer the contact time between the adsorbent and the waste, the lower the oil-fat content (Okiel This research Electro-adsorption By using activated carbon and iron electrodes, the COD removal resulted from 57.46% to 75.92% and the oil-fat removal resulted from 99.33% to 99.65%. Mohammed et al, 2011 Adsorption Final oil concentration with adsorbent weight 2-8 g for 20 minutes from 20,000 ppm is 0 ppm (100% removal) for activated carbon and 10,000 ppm (50%) for zeolite Okiel et al, 2011 Adsorption The oil removal percentage using powdered activated carbon obtained 82.6% for oil concentration 836 mg/L and 72.5% for oil concentration that increased to 1613 mg/L Xie et al, 2018 Electrochemical adsorption Waste water-based treatment using electrochemical adsorption is a treatment without the potential environmental hazard Ziati et al, 2017 Electrosorption The application of potential had a signi cant result. The adsorption without potential obtained 33.7%, whereas with the application of -0.7 and -1.4 V potential, the adsorption of chromium up to 90% and 96% Ramli and Ghazi, 2020…”
Section: E Ect Of Voltage and Time Variations On Oil-fat Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The longer the contact time between the adsorbent and the waste, the lower the oil-fat content (Okiel This research Electro-adsorption By using activated carbon and iron electrodes, the COD removal resulted from 57.46% to 75.92% and the oil-fat removal resulted from 99.33% to 99.65%. Mohammed et al, 2011 Adsorption Final oil concentration with adsorbent weight 2-8 g for 20 minutes from 20,000 ppm is 0 ppm (100% removal) for activated carbon and 10,000 ppm (50%) for zeolite Okiel et al, 2011 Adsorption The oil removal percentage using powdered activated carbon obtained 82.6% for oil concentration 836 mg/L and 72.5% for oil concentration that increased to 1613 mg/L Xie et al, 2018 Electrochemical adsorption Waste water-based treatment using electrochemical adsorption is a treatment without the potential environmental hazard Ziati et al, 2017 Electrosorption The application of potential had a signi cant result. The adsorption without potential obtained 33.7%, whereas with the application of -0.7 and -1.4 V potential, the adsorption of chromium up to 90% and 96% Ramli and Ghazi, 2020…”
Section: E Ect Of Voltage and Time Variations On Oil-fat Contentmentioning
confidence: 99%
“…Combining the two methods can be seen in its ability in the research of Xie et al (2018) , which used electrochemical adsorption and succeeded in adsorbing solid particles with sizes below 10 m with an e ciency rate of more than 90%. Research conducted by Ziati et al (2017) showed a high reduction rate using the electro-adsorption method to reduce chromium with the result reaching 96%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment methods aim at eliminating as much toxic molecules as possible which are contained in these OMW through physical, chemical, and biological processes, which can be used separately or combined. Physical treatments such as activated sludge [24] nanofiltration [25], adsorption on activated carbon [26], etc. Chemical treatments such as the use of photocatalytic membranes [27], electrohydrolysis [28], and electrocoagulation [29].…”
Section: Introductionmentioning
confidence: 99%